Penetration of oral and topical ciprofloxacin into human aqueous humor - Celebi, S; Ay, S; Aykan, Ü; Bulut, V; Alagöz, G; Celiker, ÜÖ (Scriptor Publisher, 1998)
Purpose: This study was planned to investigate the penetration of ciprofloxacin into aqueous humor following oral and topical application as a prophylactic antimicrobial agent. Methods: Forty-six patients undergoing cataract surgery were randomly divided into two groups. In the first group, the patients received 500 mg oral ciprofloxacin eight hours before surgery and in the second, 5 drops of 0.3% ciprofloxacin were applied to the patients every twenty minutes, starting 100 minutes before the surgery, By paracentesis, aqueous samples were taken just before the operation so the interval between the first topical application and paracentesis was 100 minutes. Results: The mean concentration of ciprofloxacin in aqueous humor was 0.63 +/- 0.29 mu g/ml in the first group. The concentration was 0.69 +/- 0.30 mu g/ml in the second group. Both of these mean concentrations were higher than the levels of MIC90 of S.aureus, S, epidermidis, P. aeruginosa and Gram (-) bacteriae, Conclusion: As a result, both topically and orally applied ciprofloxacin achieved a significant aqueous concentration. Each route studied might be suitable for surgical prophylaxis or treatment of infections.
Keywords: ciprofloxacin; MIC90; cataract surgery